Problematics of renewal in Al’Maqasid discourse and their impact on the movement of modern jurisprudence - Razi, Nadia (Journal of Human Sciences, 2023)
There is no doubt that contemporary studies of purposes (Al’Maqasid) have opened new horizons for research and intellectual, fundamentalist and jurisprudential view, with the uprising of thorny issues and updates, that required a methodological rejuvenation of authoring in what serves diligent and deductive view, based essentially on Maqasid (purposes) mechanisms that adapt along with the adoption of adequate tools that acting jointly with the needs of renewals. This opened the way for the withdrawal of conservatists and the accumulation of modernists looks into the matter and its renewal, creating intellectual and methodological problematics on cognitive and philosophical grounds becoming some of the biggest concerns of renewal pillars in Fikr Al’Maqasid, this led to many studies and researches in the purpose of straightening views and correcting concepts, which negatively reflected on diligence and contemporary movement of Fiqh (jurisprudence) that relies on conceptual investment in its activation in Al’Fikr, Al’Ijtihad and Fatwa.